Comparative Analysis of Financial Performance Upon Automotive Companies Registered in BEI - Mas'adah, Ninik; Megasyara, Ira; Imawan, Amrizal; Rosiawan, Rizky Wahyudha (Publisher Cv. Inara, 2021)
This research was conducted to determine the financial performance of automotive companies listed on the IDX for the period 2012 to 2015. This type of research is a quantitative descriptive study, with a total population of 13 companies and a sample of 6 automotive companies that have been selected from the population with using purposive sampling method. The data analysis method used is a comparison method consisting of a cross sectional approach and time series analysis. The results show that the results of calculations using the cross-sectional approach, automotive companies in Indonesia for the 2012-2015 period experienced fluctuations and experienced a decline in the industry average at the end of 2015 and many automotive companies were in unhealthy condition in the 2012-2015 period. Based on the results of time series analysis of automotive companies in 2012-2015, it is known that the Total Assets Turn Over has decreased, the results on Net Profit Margin have decreased, the results on the current ratio have decreased, the result of the leverage ratio has increased. The management of automotive companies in Indonesia needs to increase investment in assets, because if the level of liquidity is high but the investment in assets is small, the money or cash available will only be stored and have less value for the company.